STRATEGIES FOR INCREASING THE EFFECTIVENESS OF ECOMMERCE DEVELOPMENT MANAGEMENT IN UZBEKISTAN (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article examines strategies for increasing the effectiveness of e-commerce development management in Uzbekistan in the context of digital transformation and structural economic reforms. The study analyzes institutional, managerial, and technological factors influencing the growth and performance of e-commerce, with particular attention to governance mechanisms, regulatory frameworks, and digital infrastructure development. The research highlights key challenges constraining effective management of e-commerce development, including fragmented coordination among stakeholders, uneven digital readiness of businesses, and limitations in logistics and payment systems. At the same time, the article identifies strategic directions for improving management effectiveness through the integration of digital platforms, data-driven decision-making, support for small and medium-sized enterprises, and the alignment of national e-commerce policies with international best practices. The findings demonstrate that a comprehensive and coordinated management approach is essential for enhancing the competitiveness, sustainability, and inclusive growth of e-commerce in Uzbekistan. The results contribute to the literature on digital economy and provide policy-relevant insights for strengthening e-commerce governance and accelerating digital market development.